Ethical Issues with Using Internet of Things Devices in Citizen Science Research: A Scoping Review - Scheibner, James; Jobin, Anna; Vayena, Effy (Frontiers in Environmental Science, 2021)
Digital innovation is ever more present and increasingly integrated into citizen science research. However, smartphones and other connected devices come with specific features and characteristics and, in consequence, raise particular ethical issues. This article addresses this important intersection of citizen science and the Internet of Things by focusing on how such ethical issues are communicated in scholarly literature. To answer this research question, this article presents a scoping review of published scientific studies or case studies of scientific studies that utilize both citizen scientists and Internet of Things devices. Specifically, this scoping review protocol retrieved studies where the authors had included at least a short discussion of the ethical issues encountered during the research process. A full text analysis of relevant articles conducted inductively and deductively identified three main categories of ethical issues being communicated: autonomy and data privacy, data quality, and intellectual property. Based on these categories, this review offers an overview of the legal and social innovation implications raised. This review also provides recommendations for researchers who wish to innovatively integrate citizen scientists and Internet of Things devices into their research based on the strategies researchers took to resolve these ethical issues.
Keywords: Internet des objets; Libre accès

Blockchain et Intelligence Collective pour le Design des Connaissances de l'Internet des Objets: Modélisation du pouvoir d'agir des objets connectés - Szoniecky, Samuel (Proceedings of the 1st International Conference on Digital Tools & Uses Congress, 2018)
Cet article est une réponse prospective aux besoins de l'Internet des Objets en termes de simplicité d'utilisation, de gestion de la sécurité et de préservation de la vie privée. Nous proposons de satisfaire ces besoins à travers une plateforme d'intelligence collective utilisant des cartographies sémantiques en réalité augmentées pour récolter les interactions des utilisateurs avec des objets connectés. L'association de l'intelligence collective et des cartographies sémantiques permet d'envisager un design de connaissances où les capacités d'action des objets connectés sont facilement compréhensibles et modifiables par les utilisateurs. Dans ce dispositif, les technologies de blockchain sont utilisées pour partager en sécurité l'expression des utilisateurs et ainsi augmenter la confiance dans l'Internet des Objets et par la même contribuer au développement d'une réflexivité collective sur les usages de ces écosystèmes sociotechniques.
Keywords: Europe; France; Internet des objets; Mesure de la perception; Réservé UdeM

The Fourth Industrial Revolution (Industry 4.0): A Social Innovation Perspective - Morrar, Rabeh; Arman, Husam; Mousa, Saeed (Technology Innovation Management Review, 2017)
The rapid pace of technological developments played a key role in the previous industrial revolutions. However, the fourth industrial revolution (Industry 4.0) and its embedded technology diffusion progress is expected to grow exponentially in terms of technical change and socioeconomic impact. Therefore, coping with such transformation require a holistic approach that encompasses innovative and sustainable system solutions and not just technological ones. In this article, we propose a framework that can facilitate the interaction between technological and social innovation to continuously come up with proactive, and hence timely, sustainable strategies. These strategies can leverage economic rewards, enrich society at large, and protect the environment. The new forthcoming opportunities that will be generated through the next industrial wave are gigantic at all levels. However, the readiness for such revolutionary conversion require coupling the forces of technological innovation and social innovation under the sustainability umbrella.
Number: 11 Place: Ottawa Publisher: Talent First Network
Keywords: Canada; Internet des objets; Libre accès

Ethical Issues with Using Internet of Things Devices in Citizen Science Research: A Scoping Review - Scheibner, James; Jobin, Anna; Vayena, Effy (Frontiers in Environmental Science, 2021)
Digital innovation is ever more present and increasingly integrated into citizen science research. However, smartphones and other connected devices come with specific features and characteristics and, in consequence, raise particular ethical issues. This article addresses this important intersection of citizen science and the Internet of Things by focusing on how such ethical issues are communicated in scholarly literature. To answer this research question, this article presents a scoping review of published scientific studies or case studies of scientific studies that utilize both citizen scientists and Internet of Things devices. Specifically, this scoping review protocol retrieved studies where the authors had included at least a short discussion of the ethical issues encountered during the research process. A full text analysis of relevant articles conducted inductively and deductively identified three main categories of ethical issues being communicated: autonomy and data privacy, data quality, and intellectual property. Based on these categories, this review offers an overview of the legal and social innovation implications raised. This review also provides recommendations for researchers who wish to innovatively integrate citizen scientists and Internet of Things devices into their research based on the strategies researchers took to resolve these ethical issues.
Keywords: Internet des objets; Libre accès

The Fourth Industrial Revolution (Industry 4.0): A Social Innovation Perspective - Morrar, Rabeh; Arman, Husam; Mousa, Saeed (Technology Innovation Management Review, 2017)
The rapid pace of technological developments played a key role in the previous industrial revolutions. However, the fourth industrial revolution (Industry 4.0) and its embedded technology diffusion progress is expected to grow exponentially in terms of technical change and socioeconomic impact. Therefore, coping with such transformation require a holistic approach that encompasses innovative and sustainable system solutions and not just technological ones. In this article, we propose a framework that can facilitate the interaction between technological and social innovation to continuously come up with proactive, and hence timely, sustainable strategies. These strategies can leverage economic rewards, enrich society at large, and protect the environment. The new forthcoming opportunities that will be generated through the next industrial wave are gigantic at all levels. However, the readiness for such revolutionary conversion require coupling the forces of technological innovation and social innovation under the sustainability umbrella.
Place: Ottawa Publisher: Talent First Network
Keywords: Canada; Internet des objets; Libre accès

Blockchain et Intelligence Collective pour le Design des Connaissances de l'Internet des Objets: Modélisation du pouvoir d'agir des objets connectés - Szoniecky, Samuel (Proceedings of the 1st International Conference on Digital Tools & Uses Congress, 2018)
Cet article est une réponse prospective aux besoins de l'Internet des Objets en termes de simplicité d'utilisation, de gestion de la sécurité et de préservation de la vie privée. Nous proposons de satisfaire ces besoins à travers une plateforme d'intelligence collective utilisant des cartographies sémantiques en réalité augmentées pour récolter les interactions des utilisateurs avec des objets connectés. L'association de l'intelligence collective et des cartographies sémantiques permet d'envisager un design de connaissances où les capacités d'action des objets connectés sont facilement compréhensibles et modifiables par les utilisateurs. Dans ce dispositif, les technologies de blockchain sont utilisées pour partager en sécurité l'expression des utilisateurs et ainsi augmenter la confiance dans l'Internet des Objets et par la même contribuer au développement d'une réflexivité collective sur les usages de ces écosystèmes sociotechniques.
Keywords: Europe; France; Internet des objets; Mesure de la perception; Réservé UdeM